Physiological Disturbances of Vitamin D and some Biochemical Parameters for Coronavirus Patients - Aqdas Mohammed Sfaieh (Wasit Journal for Pure Sciences)
This study was aimed to evaluate the concentration of serum vitamin D, potassium, D-dimer, and lactate dehydrogenase (LDH) among coronavirus patients and control healthy individual according to their age ranges. The present study weel-done in AL-Zahra teaching hospital, Wasit province, Iraq; from September 2022 to February, 2023, the role of this study included 80 patients; 40 males (50.00 %) and 40 females (50.00 %) with age range (21-80 year). While, the samples of control groups consist of 60 healthy individuals, 30 males (50.00%) and 30 females (50.00%) with same age of patients group. Both study groups were separated into three age ranges; The 1st age range (21-40) year, 2nd age range (41-60) year, and the 3rd age range (61-80) year, each group of (patients and healthy subject) were separated into two subgroups (male and female).